Produksi Cabai Merah Hibrida dan Non-Hibrida dengan Penggunaan Mulsa Hitam Perak - N Nurhafsah; R Rahmi; F Fitriawaty; Ida Andriani (Fapetrik-UMPAR, 2021)
Chili is one of the commodities with a high enough economic value that needs the community and is one of the export commodities. The use of silver, black mulch (SBM) is one of the production inputs essential in increasing production. This study aims to determine the production of chili plants by applying SBM and without the application of SBM (according to farmers' habits). The research was conducted from October 2017 to January 2018 in Banggae, East Banggae District, Majene Regency. The experiment was conducted using hybrid varieties, namely Lingga, Green Temper, and Purple Temper varieties, while the non-hybrid varieties used were Pilar, Arimbi, and Darmais. The experiment consisted of three replications using a randomized block design (RBD). Observation parameters included fruit per tree, chili fruit weight, fruit length, fruit diameter, and fruit stalk length. The results showed the best application of SBM compared to not applying SBM on the parameters of fruit number, fruit weight, production, and chili fruit characteristics (fruit length, fruit diameter, and chili stalk length). Most chilies were found in the Temper Purple hybrid chili, which reached 50.45 pieces. The highest fruit weight of chili was found in the non-hybrid chili of the Darmais variety, which was 21.05 g per fruit.